Comparison of Eating Attitudes and the Susceptibility to Orthorexia Nervosa of Students in Health-Related Fields and Those in Other Fields - Hülya KAMARLI ALTUN; İlkay KESER; Selen BOZKURT (Tehran University of Medical Sciences, 2020)
Background: This study was conducted to evaluate the eating attitudes and behaviors, the susceptibility to Orthorexia nervosa and obsessive attitudes of the students who were taking undergraduate education in the field of health and the students who were not taking undergraduate education in the field of health at the time of the study. Methods: This cross-sectional study was conducted at Akdeniz University with randomly selected 304 students who were studying in the Faculty of Medicine, Nursing Law and Communication, Antalya, Turkey. Data, socio-demographic features of the students were collected using the questionnaire form consisting of Eating Attitude Test (EAT-40), The Orthorexia Nervosa Evaluation Scale (ORTO-15) and Maudsley Obsessive-Compulsive Inventory (MOCI). Results: 61.5% of the students were female. 51.9% of them were studying in the health field, while 48.1% of them were studying in other fields. At the beginning of the study, the use of ORTO-15 scale was planned to evaluate the students' orthorexic behaviors, but they were evaluated with the ORTO-11 scale because of the validity and resusceptibility of the ORTO-15 scale were found as too low. The incidence of orthorexic behavior was higher in students who were not studying in the field of health for both ORTO-15 and ORTO-11 scales. Conclusion: It is necessary to acquire healthy eating habits for university students by practical nutrition education given informal and non-formal education institutions, thus their quality of life can be increased.